Sclerosant foams - Wollmann, J. C. (Phlebologie, 2010)
Numerous ways of transferring detergent type liquid sclerosants into foam have been described. Out of all techniques, the three most commonly used around the world were selected. Sclerosant foams prepared with different agents and protocols were analyzed in detail, and their rheologic properties were assessed. Some of the results are presented in this review. Results: It is evident that the the material for foam production plays an important role for foam stability, and – connected to this – maybe also for efficacy and safety. Therefore, material that ensures acceptable foam quality should be used exclusively. Out of a huge number of possibilities, the material described in this study was found most suitable. This ensures minimal reduction of foam quality delivered into the vein. Foams considered instable are not clinically ineffective. They have a greater efficacy than the corresponding liquid agent. Foams considered stable seem to need lower injection volumes to have the same or better physical behaviour. Conclusion: Since higher volumes of sclerosant foams are correlated with more side effects, always the smallest effective volumes of foams of appropriate quality are justified.
Keywords: Sclerosant foam stability; Tessari; DSS; polidocanol; sodium tetradecyl sulfate